Semantic Technology : 6th Joint International Conference, JIST 2016, Singapore, Singapore, November 2-4, 2016 Revised Selected Papers /: 6th Joint International Conference, JIST 2016, Singapore, Singapore, November 2-4, 2016 Revised Selected Papers. (2016) - Unknown
No abstract available